TINJAUAN LITERATUR SISTEMATIS TERHADAP PEMBANGUNAN KEPARIWISATAAN YANG BERKELANJUTAN - Zaenal Abidin Mu'alim; Habibussalam Habibussalam (ipdn, 2021)
This study aims to understand the concept of sustainable tourism as an effort to reduce friction that often occurs in every level of society caused by the existence of a tourism industry that is not environmentally friendly. Some of the obstacles that are often faced by people who are in direct contact with tourism activities are health, economic and environmental problems. However, this problem has not been actively responded by academics with a comparison of the case literature. The majority of research only discusses implementation and does not take a comparative perspective between countries. This paper presents a new perspective through a systematic literature review by filtering and visualizing articles in reputable journals. To provide an overview of the direction of the concept of tourism from various countries. It was found that not all tourism activities get positive things for all communities, there is friction in every layer of society and causes various conflicts that cannot be denied due to tourism development that does not apply the principles of development. In tourism planning, it is necessary to understand the needs on many sides, understand that tourism covers a very broad aspect and sustainable tourism plans as a concept of spatial planning activities are not only related to accommodation needs, dressing tourist objects or building imaginary objects, but must be an integrated unit with a well-thought-out and measurable plan. Keywords: Systematic Literature, Tourism Industry, Sustainable Development.